Perforin Expression in Peripheral Blood Lymphatic Cells of Patients Subjected to Laparoscopic or Open Cholecystectomy - Harry Grbas; Ines Mrakovčić-Šutić; Arsen Depolo; Biserka Radošević-Stašić (Mediators of Inflammation)
Perforin-(P-) related characteristics of cytotoxic T lymphocytes and natural killer cells were investigated in peripheral blood of patients subjected to open (OC; n=23) or laparoscopic cholecystectomy (LC; n=21) and healthy controls (n=20). Blood samples were obtained preoperatively and 24 hours after the surgeries, and the data were correlated with the intensity of cholestasis and concomitant inflammation, determined by functional hepatic tests. Postoperative differences were found to be minimal: OC decreased only the percentage of CD56+ cells, while LC decreased the fraction of CD8+P+ cells and augmented the mean fluorescence intensity of P in CD56 cells. Patients elected for OC had, however, higher preoperative numbers of total P+, CD3+P+, and CD4+P+ cells than patients elected for LC and healthy controls, while both groups of patients, preoperatively, had lower fraction of CD16+P+ and CD56+P+ cells. These changes were in high correlation with blood concentrations of CRP, AP, and ALT, emphasizing the link between the preoperative cholestasis and inflammation and P-dependent cytotoxic mechanisms.